2023
DOI: 10.7150/thno.85390
|View full text |Cite
|
Sign up to set email alerts
|

Tat-NTS peptide protects neurons against cerebral ischemia-reperfusion injury via ANXA1 SUMOylation in microglia

Huijuan Zhou,
Lulu Yan,
Hezhou Huang
et al.

Abstract: Rationale: Recent studies indicate that microglial activation and the resulting inflammatory response could be potential targets of adjuvant therapy for ischemic stroke. Many studies have emphasized a well-established function of Annexin-A1 (ANXA1) in the immune system, including the regulation of microglial activation. Nevertheless, few therapeutic interventions targeting ANXA1 in microglia for ischemic stroke have been conducted. In the present study, Tat-NTS, a small peptide developed to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, our previous study reported that the cell‐penetrating peptide Tat‐NTS inhibits the binding of ANXA1 to importin β, significantly inhibiting the nuclear transport of ANXA1 in neurons and thereby protecting against ischemic stroke‐induced neuronal damage. 51 , 52 However, the present study revealed that Tat‐SIRT5‐CTM targets the SIRT5‐ANXA1 complex, resulting in SIRT5 degradation via the lysosomal pathway, which eventually alleviates microglia‐induced neuroinflammation and neuronal injury following ischemic stroke. 20 As the Tat‐NTS and Tat‐SIRT5‐CTM peptides act through different mechanisms in different cells, we supposed that a combination of the two different peptides would have greater efficacy.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, our previous study reported that the cell‐penetrating peptide Tat‐NTS inhibits the binding of ANXA1 to importin β, significantly inhibiting the nuclear transport of ANXA1 in neurons and thereby protecting against ischemic stroke‐induced neuronal damage. 51 , 52 However, the present study revealed that Tat‐SIRT5‐CTM targets the SIRT5‐ANXA1 complex, resulting in SIRT5 degradation via the lysosomal pathway, which eventually alleviates microglia‐induced neuroinflammation and neuronal injury following ischemic stroke. 20 As the Tat‐NTS and Tat‐SIRT5‐CTM peptides act through different mechanisms in different cells, we supposed that a combination of the two different peptides would have greater efficacy.…”
Section: Discussionmentioning
confidence: 66%
“…Potential neuroprotectors should be aimed at protecting nerve cells from damage and death, restoring vascular function, affecting glial, vascular and inflammatory cells, restoring nervous tissue and brain function after ischemia [ 10 , 11 , 12 ]. Promising candidates include peptide-based drugs possessing antioxidant, anti-inflammatory, regenerative, antiplatelet, and anti-apoptotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Annexin 1 (ANXA1) is a calcium-regulated phospholipid-binding protein which as gradually been recognized as an endogenous glucocorticoid-regulated anti-inflammatory mediator, which exerts potential therapeutic actions on the resolution of inflammation in several neurological disorders [18,19]. Recently, ANXA1 has gained particular interest due to its emerging properties in pain modulation and resolution [20,21].…”
Section: Introductionmentioning
confidence: 99%